Orbital Dirofilariasis Masquerading As Orbital Rhabdomyosarcoma - Farzad Pakdel; Hadi Ghadimi; Zohreh Nozarian; Fahimeh Asadi Amoli; Niloofar Pirmarzdashti; Morteza Karimi; Mohammad Mehrpour (Journal of Ophthalmic & Vision Research)
Abstract Purpose: To report a 12-year-old patient with a rapid growing orbital mass and imaging findings suggestive of rhabdomyosarcoma that was found to be dirofilariasis after mass resection. Case Report: We describe a 12-year-old patient with a rapid growing orbital mass involving medial part of orbit and medial rectus muscle and imaging findings suggestive of rhabdomyosarcoma. Histopathologic examination showed the mass to be composed of granulomatous inflammation and the thread-like object to be Dirofilaria repens. The patient was well post-operation without morbidity. In this paper, we describe distinct clinical features and imaging findings of this interesting case. Conclusion: Deep orbital lesions due to dirofilariasis, as in our case, is extremely rare. It is important to add dirofilariasis to the differential diagnosis of orbital mass lesions. Attention to the imaging clues, as provided in this report, can be helpful.